2014
DOI: 10.1037/a0035341
|View full text |Cite
|
Sign up to set email alerts
|

Teasing apart the relations between age, birth cohort, and vocational interests.

Abstract: Empirical evidence supports that aging is related to differences in work attitudes and motivation (Inceoglu, Segers, & Bartram, 2012; Kooij, de Lange, Jansen, Kanfer, & Kikkers, 2011; Ng & Feldman, 2008, 2010), but little research has explored the relations between age and vocational interests. Furthermore, recent studies of age and work attitudes suggest that generational experiences (i.e., birth year) may account for age differences in the workplace (Inceoglu et al., 2012; Ng & Feldman, 2008, 2010), which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Despite the currency of Generation Theory to help explain work values, the validity of Generation Theory may be questioned in principle, or at least queried in relation to its use. Thus, Leuty and Hansen (2014) warn of confusing the supposed effect of belonging to a certain generation on work values with the effects of ageing. There is also an assumption underpinning Generation Theory that a generation's most enduring beliefs are shaped in childhood/youth (Mannheim 1952).…”
Section: Youth Career Development and Decision-makingmentioning
confidence: 99%
“…Despite the currency of Generation Theory to help explain work values, the validity of Generation Theory may be questioned in principle, or at least queried in relation to its use. Thus, Leuty and Hansen (2014) warn of confusing the supposed effect of belonging to a certain generation on work values with the effects of ageing. There is also an assumption underpinning Generation Theory that a generation's most enduring beliefs are shaped in childhood/youth (Mannheim 1952).…”
Section: Youth Career Development and Decision-makingmentioning
confidence: 99%
“…In a review of 50 years of Strong assessment data, Hansen (1988) found interest levels were generally stable and that sex differences were resilient in many areas, especially Realistic and Artistic, but there were also small reductions of sex differences over time. Over 20 years later, in their meta-analysis of interest assessment technical manuals, Su et al (2009) found sex differences in interests were very stable over the previous four decades, with some evi-dence of smaller sex differences in Artistic and Enterprising areas in later samples, while Leuty and Hansen (2014) examined age and birth year effects in a sample of nearly 1,800 adults using data from 1974 through 1995 and three forms of the Strong assessment, finding small effects of both age and year. Together, these reviews suggest a slight narrowing of sex differences from the 1930s through the 2000s, but otherwise relatively little change.…”
Section: Year Effects On Vocational Interestsmentioning
confidence: 99%
“…Su et al (2009) describe sex differences in vocational interests as “substantial” (p. 873) and “an exception to the findings that sex differences are small to nonexistent” (p. 873), yet their effect size and overlap estimates might lead others to conclude that sex differences are roughly medium, based on prevailing interpretive standards of .2 for a small effect, .5 for a medium effect, and .8 for a large effect (Cohen, 1992). Indeed, Leuty and Hansen (2014), summarizing much of the same interest literature cited above concluded “overall the interests of women and men are more similar than different” (p. 291).…”
Section: Overall Sex Differencesmentioning
confidence: 99%
“…However, crosssectional age differences (as we examine in this study) can also reflect generational or cohort differences, such that people born at specific time periods may have been exposed to different factors that impacted their interests. Prior research indicates that generational differences in interests tend to be small, with the only significant difference being that younger generations tend to have weaker realistic interests (Leuty & Hansen, 2014).…”
Section: The Popularity Of Interest Profiles Across Sociodemographic ...mentioning
confidence: 99%